Polyphasic Taxonomy of Species within the Dermatophyte Genus Arthroderma Including A. fimbriatum sp. nov and A. cellare sp. nov - Frederik Baert; Paulien Lefevere; Goens Karine; Roelke De Paepe; Elizabet D’hooge; Pierre Becker; Ann Packeu (Mycopathologia, 2026)

Towards a sustained and fit-for-purpose European ocean observing and forecasting system - Toste Tanhua; Pierre-Yves Le Traon; Nicole Köstner; Dina Eparkhina; Gabriel Navarro; Martha Bonnet Dunbar; Sabrina Speich; Ananda Pascual; Karina von Schuckmann; Giovanni Liguori; Johannes Karstensen; Abed El Rahman Hassoun; et al. (Frontiers in Marine Science, 2024)
The EU funded project EuroSea brought together key actors of the European ocean observing and forecasting communities with key users of the ocean observing products and services in order to better integrate existing ocean observation systems and tools, and to improve the delivery of ocean information to users. EuroSea was constructed around the ocean observing value chain that connects observations to users of ocean information, and, just as intended, the value chain concept was a useful prism to improve the system. In this article, we summarize some of the main take-home messages from EuroSea on the needs for developing the European Ocean Observing System and its links with modeling and forecasting systems. During the project, the challenges and gaps in the design and coordination of the European ocean observing and forecasting system were identified and mapped. Many gaps and challenges related to the observations of physical, chemical and biological Essential Ocean Variables were identified. Some of these gaps are related to technological developments, while others are caused by insufficient and short-term funding leading to a not sustainable system, management, and cooperation between different entities, as well as limitations in foresight activities, policies and decisions. This article represents a compilation of the broader needs for advancing the observing and forecasting system, and is meant as a guide for the community, and to funders and investors to advance ocean observing and the delivery of ocean information in Europe. To enhance the sustainability of ocean observations, which is paramount for a reliable provision of quality oceanographic data and services, several recommendations were compiled for ocean observing networks, frameworks, initiatives, as well as the ocean observing funders within the European nations, and the European Commission.

Continuous real-time monitoring of formaldehyde over 5 weeks in two French primary schools: identification of the relevant time resolution and the most appropriate ventilation scenario - Claire Trocquet; Irene Lara-Ibeas; Anaïs Becker; Aurélie Schulz; Pierre Bernhardt; Vincent Person; Béatrice Cormerais; Stéphanette Englaro; Stéphane Le Calvé (Air Quality, Atmosphere & Health, 2023)

The ecologically relevant genetics of plant–plant interactions - Claude Becker; Richard Berthomé; Philippe Delavault; Timothée Flutre; Hélène Fréville; Stéphanie Gibot-Leclerc; Valérie Le Corre; Jean-Benoit Morel; Nathalie Moutier; Stéphane Muños; Céline Richard-Molard; James Westwood; et al. (Trends in Plant Science, 2023)

Climate variability and aridity modulate the role of leaf shelters for arthropods: A global experiment - Gustavo Q. Romero; Thiago Gonçalves‐Souza; Tomas Roslin; Robert J. Marquis; Nicholas A.C. Marino; Vojtech Novotny; Tatiana Cornelissen; Jerome Orivel; Shen Sui; Gustavo Aires; Reuber Antoniazzi; Wesley Dáttilo; et al. (Global Change Biology, 2022)
Current climate change is disrupting biotic interactions and eroding biodiversity worldwide. However, species sensitive to aridity, high temperatures, and climate variability might find shelter in microclimatic refuges, such as leaf rolls built by arthropods. To explore how the importance of leaf shelters for terrestrial arthropods changes with latitude, elevation, and climate, we conducted a distributed experiment comparing arthropods in leaf rolls versus control leaves across 52 sites along an 11,790 km latitudinal gradient. We then probed the impact of short‐ versus long‐term climatic impacts on roll use, by comparing the relative impact of conditions during the experiment versus average, baseline conditions at the site. Leaf shelters supported larger organisms and higher arthropod biomass and species diversity than non‐rolled control leaves. However, the magnitude of the leaf rolls’ effect differed between long‐ and short‐term climate conditions, metrics (species richness, biomass, and body size), and trophic groups (predators vs. herbivores). The effect of leaf rolls on predator richness was influenced only by baseline climate, increasing in magnitude in regions experiencing increased long‐term aridity, regardless of latitude, elevation, and weather during the experiment. This suggests that shelter use by predators may be innate, and thus, driven by natural selection. In contrast, the effect of leaf rolls on predator biomass and predator body size decreased with increasing temperature, and increased with increasing precipitation, respectively, during the experiment. The magnitude of shelter usage by herbivores increased with the abundance of predators and decreased with increasing temperature during the experiment. Taken together, these results highlight that leaf roll use may have both proximal and ultimate causes. Projected increases in climate variability and aridity are, therefore, likely to increase the importance of biotic refugia in mitigating the effects of climate change on species persistence.

Subtle structures with not‐so‐subtle functions: A data set of arthropod constructs and their host plants - Cássio Cardoso Pereira; Samuel Novais; Milton Barbosa; Daniel Negreiros; Thiago Gonçalves‐Souza; Tomas Roslin; Robert Marquis; Nicholas Marino; Vojtech Novotny; Jerome Orivel; Shen Sui; Gustavo Aires; et al. (Ecology, 2022)
The construction of shelters on plants by arthropods might influence other organisms via changes in colonization, community richness, species composition, and functionality. Arthropods, including beetles, caterpillars, sawflies, spiders, and wasps often interact with host plants via the construction of shelters, building a variety of structures such as leaf ties, tents, rolls, and bags; leaf and stem galls, and hollowed out stems. Such constructs might have both an adaptive value in terms of protection (i.e., serve as shelters) but may also exert a strong influence on terrestrial community diversity in the engineered and neighboring hosts via colonization by secondary occupants. Although different traits of the host plant (e.g., physical, chemical, and architectural features) may affect the potential for ecosystem engineering by insects, such effects have been, to a certain degree, overlooked. Further analyses of how plant traits affect the occurrence of shelters may therefore enrich our understanding of the organizing principles of plant‐based communities. This data set includes more than 1000 unique records of ecosystem engineering by arthropods, in the form of structures built on plants. All records have been published in the literature, and span both natural structures (91% of the records) and structures artificially created by researchers (9% of the records). The data were gathered between 1932 and 2021, across more than 50 countries and several ecosystems, ranging from polar to tropical zones. In addition to data on host plants and engineers, we aggregated data on the type of constructs and the identity of inquilines using these structures. This data set highlights the importance of these subtle structures for the organization of terrestrial arthropod communities, enabling hypotheses testing in ecological studies addressing ecosystem engineering and facilitation mediated by constructs. There are no copyright restrictions and please cite this paper when using the data in publications.

Incidence rates and contemporary trends in primary urethral cancer - Mike Wenzel; Luigi Nocera; Claudia Collà Ruvolo; Christoph Würnschimmel; Zhe Tian; Shahrokh F. Shariat; Fred Saad; Alberto Briganti; Derya Tilki; Philipp Mandel; Andreas Becker; Luis A. Kluth; et al. (Cancer Causes & Control, 2021)
Purpose We assessed contemporary incidence rates and trends of primary urethral cancer. Methods We identified urethral cancer patients within Surveillance, Epidemiology and End Results registry (SEER, 2004–2016). Age-standardized incidence rates per 1,000,000 (ASR) were calculated. Log linear regression analyses were used to compute average annual percent change (AAPC). Results From 2004 to 2016, 1907 patients with urethral cancer were diagnosed (ASR 1.69; AAPC: -0.98%, p = 0.3). ASR rates were higher in males than in females (2.70 vs. 0.55), respectively and did not change over the time (both p = 0.3). Highest incidence rates were recorded in respectively ≥75 (0.77), 55–74 (0.71) and ≤54 (0.19) years of age categories, in that order. African Americans exhibited highest incidence rate (3.33) followed by Caucasians (1.72), other race groups (1.57) and Hispanics (1.57), in that order. A significant decrease occurred over time in Hispanics, but not in other race groups. In African Americans, male and female sex-stratified incidence rates were higher than in any other race group. Urothelial histological subtype exhibited highest incidence rate (0.92), followed by squamous cell carcinoma (0.41), adenocarcinoma (0.29) and other histologies (0.20). In stage stratified analyses, T 1 N 0 M 0 stage exhibited highest incidence rate. However, it decreased over time (−3.00%, p = 0.02) in favor of T 1-4 N 1-2 M 0 stage (+ 2.11%, p = 0.02). Conclusion Urethral cancer is rare. Its incidence rates are highest in males, elderly patients, African Americans and in urothelial histological subtype. Most urethral cancer cases are T 1 N 0 M 0 , but over time, the incidence of T 1 N 0 M 0 decreased in favor of T 1-4 N 1-2 M 0 .

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Bladder cancer stage and mortality: urban vs. rural residency - Marina Deuker; L. Franziska Stolzenbach; Claudia Collà Ruvolo; Luigi Nocera; Zhe Tian; Frederik C. Roos; Andreas Becker; Luis A. Kluth; Derya Tilki; Shahrokh F. Shariat; Fred Saad; Felix K.H. Chun; et al. (Cancer Causes & Control, 2021)
Objective Relative to urban populations, rural patients may have more limited access to care, which may undermine timely bladder cancer (BCa) diagnosis and even survival. Methods We tested the effect of residency status (rural areas [RA < 2500 inhabitants] vs. urban clusters [UC ≥ 2500 inhabitants] vs. urbanized areas [UA, ≥50,000 inhabitants]) on BCa stage at presentation, as well as on cancer-specific mortality (CSM) and other cause mortality (OCM), according to the US Census Bureau definition. Multivariate competing risks regression (CRR) models were fitted after matching of RA or UC with UA in stage-stratified analyses. Results Of 222,330 patients, 3496 (1.6%) resided in RA, 25,462 (11.5%) in UC and 193,372 (87%) in UA. Age, tumor stage, radical cystectomy rates or chemotherapy use were comparable between RA, UC and UA (all p > 0.05). At 10 years, RA was associated with highest OCM followed by UC and UA (30.9% vs. 27.7% vs. 25.6%, p < 0.01). Similarly, CSM was also marginally higher in RA or UC vs. UA (20.0% vs. 20.1% vs. 18.8%, p = 0.01). In stage-stratified, fully matched CRR analyses, increased OCM and CSM only applied to stage T1 BCa patients. Conclusion We did not observe meaningful differences in access to treatment or stage distribution, according to residency status. However, RA and to a lesser extent UC residency status, were associated with higher OCM and marginally higher CSM in T1N0M0 patients. This observation should be further validated or refuted in additional epidemiological investigations.

High thematic resolution land use change models refine biodiversity scenarios: A case study with Belgian bumblebees - Leon Marshall; Veronique Beckers; Sarah Vray; Pierre Rasmont; Nicolas J. Vereecken; Nicolas Dendoncker (Journal of Biogeography, 2021)
Aim Projections of biodiversity scenarios often rely solely on climate change to inform species distribution shifts in the future. Land use projections are rarely used due to their unavailability and, when available, are often at coarse spatial and thematic resolutions, making them unsuitable to capture fine scale habitat suitability. This study aims to (a) show how coupled land use change (LUC) models of high thematic resolution (HTR) can be used in species distribution models (SDM), (b) compare the impacts of HTR and low thematic resolution (LTR) explanatory predictors on biodiversity scenarios and (c) assess the impact of species' present area of occupancy on the effect of thematic resolution in SDMs. Location Belgium Taxon Bumblebees ( Bombus ) Methods We compared species distribution models with 17 land use predictors (HTR) against models with 5 land use predictors (LTR). We modelled the distribution of 17 bumblebee species in Belgium projected until 2035. We examined how model performance, variable importance and projections of distribution change differed depending on the thematic resolution of the land use predictors. Results Overall, HTR models performed better than LTR models. LTR models predicted greater extent per species. HTR projected a greater percentage of range gains, and both models projected similar losses of suitable habitat. However, the percentage loss and connectivity of suitable habitats varied differently for HTR and LTR models along a gradient of rare to common species. The HTR models projected greater loss of suitable areas for rare species and less loss for common species compared to LTR models. Main conclusions These results illustrate the importance of using ecologically relevant explanatory variables in SDMs, particularly for rare and localized species with specific habitat requirements. The results also indicate the need for large‐scale LUC projections to improve future biodiversity scenarios under climate change and to improve the ability of conservationists and policymakers to use SDM projections.

Discrepancies in Flood Modelling Approaches in Transboundary River Systems: Legacy of the Past or Well-grounded Choices? - Vasileios Kitsikoudis; Bernhard P. J. Becker; Ymkje Huismans; Pierre Archambeau; Sébastien Erpicum; Michel Pirotton; Benjamin Dewals (Water Resources Management, 2020)

Tomato leaf curl Kunene virus: a novel tomato-infecting monopartite begomovirus from Namibia - Jean-Michel Lett; Jocelin Ncho; Sohini Claverie; Murielle Hoareau; Pierre Lefeuvre; Vera De Cauwer; Rolf Becker (Archives of Virology, 2020)

Effect of Intrastriatal 6-OHDA Lesions on Extrastriatal Brain Structures in the Mouse - Birte Becker; Melek Demirbas; Sonja Johann; Adib Zendedel; Cordian Beyer; Hans Clusmann; Stefan Jean-Pierre Haas; Andreas Wree; Sonny Kian Hwie Tan; Markus Kipp (Molecular Neurobiology, 2017)

Climatic variations explain annual fluctuations in French Périgord black truffle wholesale markets but do not explain the decrease in black truffle production over the last 48 years - François Le Tacon; Benoît Marçais; Michel Courvoisier; Claude Murat; Pierre Montpied; Michel Becker (Mycorrhiza, 2014)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

GODAE: The Global Ocean Data Assimilation Experiment - Michael Bell; Michel Lefèbvre; Pierre-Yves Le Traon; Neville Smith; Kirsten Wilmer-Becker (Oceanography, 2009)

Differential invasion success among biotypes: case of Bemisia tabaci - Hélène Delatte; Pierre-François Duyck; Aurélie Triboire; Patrice David; Nathalie Becker; Olivier Bonato; Bernard Reynaud (Biological Invasions, 2009)

Senescence rates are determined by ranking on the fast–slow life‐history continuum - Owen R. Jones; Jean‐Michel Gaillard; Shripad Tuljapurkar; Jussi S. Alho; Kenneth B. Armitage; Peter H. Becker; Pierre Bize; Jon Brommer; Anne Charmantier; Marie Charpentier; Tim Clutton‐Brock; F. Stephen Dobson; et al. (Ecology Letters, 2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar‐sized birds. These generalizations have been challenged because of limitations of life‐table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual‐based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life‐table approach. Focusing on one aspect of life history – survival or recruitment – can provide reliable information on overall senescence.

Speleoseismology: A critical perspective - Arnfried Becker; Colin A. Davenport; Urs Eichenberger; Eric Gilli; Pierre-Yves Jeannin; Corinne Lacave (Journal of Seismology, 2006)

Eocene-Pliocene time scale and stratigraphy of the Upper Rhine Graben (URG) and the Swiss Molasse Basin (SMB) - Jean-Pierre Berger; Bettina Reichenbacher; Damien Becker; Matthias Grimm; Kirsten Grimm; Laurent Picot; Andrea Storni; Claudius Pirkenseer; Andreas Schaefer (International Journal of Earth Sciences, 2005)

Paleogeography of the Upper Rhine Graben (URG) and the Swiss Molasse Basin (SMB) from Eocene to Pliocene - Jean-Pierre Berger; Bettina Reichenbacher; Damien Becker; Matthias Grimm; Kirsten Grimm; Laurent Picot; Andrea Storni; Claudius Pirkenseer; Christian Derer; Andreas Schaefer (International Journal of Earth Sciences, 2005)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)